Early Onset Immune-Related Adverse Event to Identify Pseudo-Progression in a Patient With Ovarian Cancer Treated With Nivolumab: A Case Report and Review of the Literature - Li, Hui; Zhou, Xin; Zhang, Ding; Wang, Guoqiang; Cheng, Xiaochun; Xu, Caihong; Yao, Bin; Pang, Linrong; Chen, Jun (Frontiers in Medicine, 2020)
Background: Immune checkpoint inhibitors (ICIs) have shown clinical benefit in many advanced tumors, however, pseudo-progression is a noted phenomenon of ICIs characterized by radiologic enlargement of the tumor burden, followed by regression. How to differentiate pseudo-progression from progression remains a critical clinical issue. Recent studies have demonstrated the association between immune-related adverse events (irAEs) and efficacy of ICIs. Here we demonstrated an ovarian cancer patient treated with nivolumab in whom the early-onset irAE was identified to differentiate pseudo-progression from progression. Case presentation: Here we present the case of a 47-year-old woman with histopathologically confirmed diagnosis of metastatic ovarian cystadenocarcinoma. Immunohistochemical examination showed 10% of tumor cells to express the programmed cell death receptor ligand 1 (PD-L1) and a 381-gene panel sequencing in a College of American Pathologists (CAP) certificated lab revealed a moderate mutational tumor burden with 5.7 Mutants/Mb. The patient received nivolumab 100 mg every 2 week as a fourth line treatment. Within the first 2 months, the tumor volume increased by 23.6%. However, the patient experienced an elevation of Alanine aminotransferase (ALT) and Aspartate aminotransmerase (AST), which was diagnosed as the immune-related hepatitis. Thus the treatment continued and afterwards, the patient reached a partial response (PR) to nivolumab and the progression-free survival was 9 months. Conclusion: To our knowledge, this is the first case describing early-onset immune-related adverse events to identify pseudo-progression in a patient with ovarian cancer treated with nivolumab, and PD-L1 expression level may be a predictive biomarker in the immunotherapy of ovarian cancer.